Long-lived isomers in neutron-rich Z=72-76 nuclides - Reed, Matthew; Stöhlker, Thomas (Physical review. C, Nuclear physics, 2012)
A study of neutron-rich isotopes in the A=185 region of the nuclear chart has uncovered long-lived (>1s) isomers in several isotopes of hafnium, tantalum, tungsten, rhenium, and osmium. The region was accessed via the use of projectile fragmentation with the UNILAC-SIS accelerators at GSI. Fragmentation products of 197Au were passed through the fragment separator (FRS) and injected into the experimental storage ring (ESR), where single-ion identifications could be made. Evidence is presented for isomers in 183184 186Hf, 186187Ta,186W, 190192 194Re, and 195Os with excitation energies in the range of 0.13.0 MeV. The lightest of these nuclides have well deformed prolate shapes, while the heaviest are transitional and susceptible to shape changes. Their properties are interpreted with the help of multi-quasiparticle and potential-energy- surface calculations. ©2012 American Physical Society.